CD34+CD19-CD22+ B-cell progenitors might underlie phenotypic escape in patients treated with CD19-directed therapies - Bueno, C; Barrena, S; Bataller, A; Ortiz-Maldonado, V; Elliott, N; O'Byrne, S; Wang, G; Rovira, M; Gutierrez-Agüera, F; Trincado, JL; Gonzalez, M; Morgades, M; et al. (American Society of Hematology, 2022)
CD19-directed immunotherapies have revolutionized the treatment of advanced B-ALL. Despite initial impressive rates of complete remission (CR) many patients ultimately relapse. B-ALL patients successfully treated with CD19-directed T-cells eventually relapse, which coupled with the early onset of CD22 expression during B-cell development suggests that pre-existing CD34+CD22+CD19- (pre)-leukemic cells could represent an "early progenitor origin-related" mechanism underlying phenotypic escape to CD19-directed immunotherapies. We demonstrate that CD22 expression precedes CD19 expression during B-cell development. CD34+CD19-CD22+ cells are found in diagnostic and relapsed BM samples of ~70% B-ALL patients, and their frequency increases 2-fold in B-ALL patients in CR after CD19-CAR T-cell therapy. The median of CD34+CD19-CD22+ cells before treatment was 3-fold higher in B-ALL patients who relapse after CD19-directed immunotherapy (median follow-up of 24 months). FISH analysis in flow-sorted populations and xenograft modeling revealed that CD34+CD19-CD22+ cells harbor the genetic abnormalities present at diagnosis and initiate leukemogenesis in vivo. Our data suggest that pre-leukemic CD34+CD19-CD22+ progenitors may underlie phenotypic escape after CD19-directed immunotherapies and reinforce ongoing clinical studies aimed at CD19/CD22 dual-targeting as a strategy to reduce CD19- relapses. The implementation of such CD34/CD19/CD22 immunophenotyping in clinical laboratories for initial diagnosis and subsequent monitoring of B-ALL patients during CD19-targeted therapy is encouraged.